Pengembangan Media Pembelajaran Game Aritmatika (GAMETIKA) Menggunakan Adobe Flash CS6 - Galandaru Swalaganata (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2018)
Mathematical sciences that study basic mathematical operations that is addition, subtraction, multiplication, and division are arithmetic. Arithmetic lessons have been introduced since entering formal education. It can deliver with various ways, one of them is using a line of numbers or represent with objects, such as marbles, books, and pencils. As the development of science and technology, the delivery process can be done by using mobile devices. For example smartphones, tablets and laptops. Utilization can be done by making games or more commonly known as ICT-based learning media. With the game related to math, users can not only play games, but also can sharpen the ability to solve problems related to math. Gametika made with Adobe Flash Professional CS6 software and Adobe Air 3.2 application runtime with waterfall design model consisting of: (1) system requirement analysis; (2) design system; (3) implementation; (4) trials; (5) deployment; and (6) treatment. This game can run on a smartphone with Android 4.0 Ice Cream Sandwich operating system or a newer android version and smartphone screen resolution of at least 320 x 480 pixels. Gametika can also be played on a PC or laptop. The validation results are declared valid and suitable for use especially for children aged 10-13 years.